„Židé Afriky“ Vznik a současná podoba představy o židovském původu nigerijského etnika Igbo - Hana Štěpánková (AntropoWebzin, 2010)
Members of the Igbo (sometimes also Ibo) ethnic group from the Southeast region of Nigeria very often consider themselves to be Jews. The article examines this phenomenon from a historical and anthropological perspective.The first part deals with how this notion came into being, considers the perceptions which preceded it and examines how ideologies added new meaning. It discusses slavery and colonialism on the one hand and abolitionism and decolonisation on the other.The second part focuses on the contemporary manifestation of this notion, i.e. on the Igbo belief in the Jewish origins of their own group, and suggests that this could be interpreted as a sign of Igbo nationalism. The implementation of national symbols is demonstrated on strategies which prove their Jewish origin. The examples are drawn from my own research among Igbos living in the Czech Republic as well as from Internet articles written by fellow Igbos in other countries.